A cytosolic chaperone complexes with dynamic membrane J-proteins and mobilizes a nonenveloped virus out of the endoplasmic reticulum. - Christopher Paul Walczak; Madhu Sudhan Ravindran; Takamasa Inoue; Billy Tsai (PLoS Pathogens)
Nonenveloped viruses undergo conformational changes that enable them to bind to, disrupt, and penetrate a biological membrane leading to successful infection. We assessed whether cytosolic factors play any role in the endoplasmic reticulum (ER) membrane penetration of the nonenveloped SV40. We find the cytosolic SGTA-Hsc70 complex interacts with the ER transmembrane J-proteins DnaJB14 (B14) and DnaJB12 (B12), two cellular factors previously implicated in SV40 infection. SGTA binds directly to SV40 and completes ER membrane penetration. During ER-to-cytosol transport of SV40, SGTA disengages from B14 and B12. Concomitant with this, SV40 triggers B14 and B12 to reorganize into discrete foci within the ER membrane. B14 must retain its ability to form foci and interact with SGTA-Hsc70 to promote SV40 infection. Our results identify a novel role for a cytosolic chaperone in the membrane penetration of a nonenveloped virus and raise the possibility that the SV40-induced foci represent cytosol entry sites.